MENINGKATKAN KREATIFITAS DAN INOVASI MELALUI PERMAINAN MAKE SOMETHING BEAUTIFUL - Paramita Nuraini; Subiyanto Subiyanto; Nofi Nur Yuhenita (STMIK Royal, 2020)
Abstract: The low creativity of students at Muhammadiyah High School in Magelang is the background in this service. This lack of creativity is related to creativity in thinking and creativity. Many students do not participate in teaching and learning activities as much as passive and monotonous students in learning. This dedication uses innovative Guidance Counseling media that is using the game